2008
DOI: 10.1088/0952-4746/28/3/008
|View full text |Cite
|
Sign up to set email alerts
|

226Ra,232Th and40K contents in soil samples from Garhwal Himalaya, India, and its radiological implications

Abstract: The exposure of human beings to ionising radiation from natural sources is a continuing and inescapable feature of life on earth. Natural radionuclides are widely distributed in various geological formations and ecosystems such as rocks, soil groundwater and foodstuffs. In the present study, the distribution of (226)Ra, (232)Th and (40)K was measured in soil samples collected from different lithological units of the Thauldhar and Budhakedar regions of Garhwal Himalaya, India. The collected soil samples were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 13 publications
0
22
3
Order By: Relevance
“…e overall mean activity for the data in this table was calculated to be 14.3 ± 3.8, 17.3 ± 4.2, and 1300 ± 300 for 238 U, 232 , and 40 K, respectively. However, the specific activity of 40 K obtained in this study is higher than the global mean value of 420Bqkg −1 [15].…”
Section: Resultscontrasting
confidence: 80%
See 2 more Smart Citations
“…e overall mean activity for the data in this table was calculated to be 14.3 ± 3.8, 17.3 ± 4.2, and 1300 ± 300 for 238 U, 232 , and 40 K, respectively. However, the specific activity of 40 K obtained in this study is higher than the global mean value of 420Bqkg −1 [15].…”
Section: Resultscontrasting
confidence: 80%
“…From Figure 1, the specific activity of 40 K reported in this study is lower than values reported in Narok, Kenya [10], but higher than the global average value [15] and values reported in other parts of the world [5,[11][12][13][14]. 238 U recorded in this study is lower than the worldwide mean [15] and values obtained in [5,10,13,14] but higher than values reported in [11,12].…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…The particular peak of the gamma spectra was measured using the reference of 661 keV of 137 Cs. The activity concentrations in these samples were calculated from the intensity of each line in the spectrum, taking into account the mass, the geometry of the samples, the counting time and the efficiency of the detector (12) .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Studies on soil samples from different lithological units have suggested that the distribution of radionuclides depends on rock formation, their chemical properties and sample origin (Malakhov et al, 1966;Rao et al, 1996;Levin et al, 2002;Ramola et al, 2008;Baskaran, 2011). Rani and Singh (2005) (Singh et al, 2003).…”
Section: Resultsmentioning
confidence: 99%